Mineral particles in the lungs of subjects resident in the Rome area and not occupationally exposed to mineral dust - Paoletti, L; Batisti, D; Caiazza, S; Petrelli, M G; Taggi, F; De Zorzi, L; Dina, M A; Donelli, G (Environmental research, 1987)
We studied the inorganic particulate contained in the lung parenchyma of 10 subjects (5 males and 5 females) resident in an urban area and not occupationally exposed to dusts. A total of 17 mineral types were identified, along with 16 metal elements in the form of oxides and sulfides. Approximately 70% of the minerals were made up of phyllosilicates, in particular clay, mica, and talc; three metal elements, Fe, Al, and Ti, accounted for more than 75% of the recovered oxide particles. The mean concentration of the observed inorganic particles was approximately 1.8 X 10(5) pp/mg dry tissue. No significant differences were observed in terms of total particulate concentration in the various areas of the lungs and between the right and left lung. Instead we observed a larger concentration of fibrous particles in the upper lobes. The analysis of the data made it possible to determine the presence of a high degree of correlation between the concentrations of silicates and the concentrations of metal oxides and sulfides, implying the existence of a ubiquitous environmental source of these mineral particles. The frequent observation of tremolite fibers is remarkable. This finding, confirmed elsewhere, indicates that the magnitude of the sources of these fibers in the environment, constituted by contaminated talc dusts, has been underestimated until today.